Male ignorance and equal blameworthiness - Tan, Benjamin Yong Kiat (Nanyang Technological University, 2024)
Are misogynistic men who are wilfully ignorant of their misogyny equally blameworthy for their actions to knowing misogynistic men? Equal Culpability Thesis and conventional accounts that attempt to prove this thesis fall short when applied to cases of misogyny. This paper will show that wilful hermeneutical ignorance present in misogyny adds more conditions to the conventional account and changes the amount of blameworthiness a wilfully ignorant misogynist is liable for.